Future Time Perspective Associated With Career Maturity Among Final Year Students: Perspektif Waktu Masa Depan yang Berkaitan dengan Kematangan Karier di Kalangan Mahasiswa Tingkat Akhir - Maghfiroh Imega Triyaninda; Widyastuti (Universitas Muhammadiyah Sidoarjo, 2025)
General Background Career preparation represents a central developmental task during early adulthood, particularly for university students approaching graduation who must make informed occupational decisions aligned with personal competencies and labor market demands. Specific Background Final-year students frequently encounter uncertainty in career planning, limited occupational information, and difficulty making independent career decisions, indicating varying levels of career maturity. Future Time Perspective is considered a psychological construct reflecting individuals’ perceptions of opportunities and limitations related to their future goals and planning processes. Knowledge Gap Although career maturity has been widely discussed, empirical examination of its statistical relationship with Future Time Perspective among final-year university students remains limited within specific institutional contexts. Aims This study aims to investigate the relationship between Future Time Perspective and career maturity among final-year students at Universitas Muhammadiyah Sidoarjo. Results Using a quantitative correlational design with quota sampling involving 162 students, data analyzed through Spearman correlation revealed a significant positive relationship between Future Time Perspective and career maturity (r = 0.761, p < 0.001). Most respondents demonstrated moderate levels of both Future Time Perspective (72%) and career maturity (65%). Novelty The study provides empirical evidence linking psychological future orientation with career development readiness using validated measurement scales within a higher education population. Implications The findings indicate that clearer future orientation is associated with higher readiness in career decision processes, offering empirical references for career guidance initiatives and student developmental programs in higher education settings. Highlights: Statistical Analysis Identified a Strong Positive Correlation Between Psychological Future Orientation and Readiness for Occupational Decision Making. Majority of Participants Demonstrated Moderate Levels Across Both Measured Psychological Constructs. Empirical Data Derived From 162 Undergraduate Respondents Using Validated Psychometric Instruments and Spearman Correlation Analysis. Keywords: Future Time Perspective, Career Maturity, Final Year Students,, Career Development, Quantitative Correlational Study